Total Phenolic and Flavonoid Content and Antioxidant Activity of Vitex Montevidensis (Spreng) Moldenke - Verbenaceae - Onofre, Sideney Becker; Abatti, Dirceu; Tessaro, Amarildo Antonio; Tessaro, Alessandra Buss (Ciência e Natura, 2016)
In recent years, a substantial amount of evidence has pointed to the key role of free radicals and other oxidants as the main culprits for aging and degenerative diseases associated with aging, such as cancer, cardiovascular diseases, cataract, decline of the immune system and brain dysfunctions. The objective of this work was therefore to detect variations in total phenol and flavonoid content, and in antioxidant activity of samples of V. montevidensis. Dried samples were submitted to extraction to obtain the hexane, ethyl acetate and ethanol fractions. Phytochemical prospecting and an analysis of the phenolic content and antioxidant activity was carried out. The data was analyzed according to the mean±standard deviation and submitted to analysis of variance followed by Tukey's test with a significance of (p < 0.05). Flavonoids, tannins, coumarins, terpenoids, steroids, alkaloids and anthraquinones were detected in the samples. The content of total flavonoids varied between 3.18±0,58 and 7.22±0,17 g/100g, while the total phenols ranged from 1.13±0.16 to 18.44±0.21 g/100g. The extracts produced EC50 between 339.75±6.56 and 278.33±23.11 μg/mL.